Bakteri dominan di dalamsaluran akar gigi nekrosis (Dominant bacteria in root canal of necrotic teeth) - Irfan Fauzy Yamin; Nurhayaty Natsir (Journal of Dentomaxillofacial Science, 2014)
One disease that often affects the pulp is necrotic teeth, which are caused by some irritants. Most major irritants aremicrobes, such as bacteria. This study aimed to determine the type of bacteria in the necrotic root canal. Samples wereobtained from fifteen patients with necrotic teeth in Conservation Clinic of Dental Hospital, Faculty of Dentistry,Hasanuddin University. Specimens of bacteria from samples taken using paper points were inserted into the root canal.The specimens identified in the Laboratory of Microbiology, Faculty of Medicine. The results showed that there areseven types of bacteria that vary in number, most are gram-positive facultative anaerobic bacteria Actinomyces spp. Itwas concluded that Actinomyces spp. is the dominant species of bacteria on the necrotic tooth root canal.